Communication Between Husband and Wife Who Do Not Have Children - Adha, Sarah Tazkiyatun Nufus; Soedarsono, Dewi K (Yayasan Sembilan Pemuda Indonesia, 2024)
This study 1) recognize and characterize the interpersonal communication styles of a husband and wife without children; 2) Assess the impact of interpersonal communication on the quality of relationships between husband and wife who do not yet have children; 3) Identify the strategies and mechanisms used by estranged relatives who do not have children to address communication challenges in their relationships; and 4) Offering practical advice to marriage counselors based on the results of their research. The qualitative research approach was used to understand events in life from the viewpoint of the one going through them. The finding showed that Husband and wife interactions not accompanied by children are typically more passionate and emotional. Social pressure, expectations from the extended family, and feelings of inferiority are some of the difficulties faced by a husband and wife who are not yet parents. Open and sincere communication styles are typically employed by harmonious couples. This kind of support lessens stress and makes the emotional connection between a husband and wife stronger. New insights into the subject of communication studies are offered by this study. This study takes a holistic approach, taking into account several variables that affect communication, such as emotional support, cultural expectations, and social pressure. This study pinpoints the successful communication techniques employed by harmonious couples, offering helpful advice to other couples in like circumstances. This study offers a fresh viewpoint on the function of social support in the dynamics of marital communication by highlighting the significance of emotional support from a range of sources in assisting couples in overcoming stress and obstacles.